Demonstrating the Protective Efficacy of the Novel Fluoroquinolone Finafloxacin against an Inhalational Exposure to Burkholderia pseudomallei - Barnes, Kay B. (Antimicrob Agents Chemother, 2017)
Burkholderia pseudomallei is the causative agent of melioidosis, a serious disease endemic in Southeast Asia and Northern Australia. Antibiotic treatment is lengthy and relapse often occurs. Finafloxacin is a novel fluoroquinolone with increased antibacterial activity in acidic conditions in contrast to other fluoroquinolones which demonstrate reduced activity at a lower pH. Therefore, finafloxacin may have improved efficacy against B. pseudomallei, which can survive within host cells where the local pH is acidic. In vitro analysis was performed using MICs, minimal bactericidal concentrations (MBCs), time-kill assays, persister cell assays, and macrophage assays. Finafloxacin showed increased bactericidal activity at pH 5 in comparison to pH 7 and ciprofloxacin at pH 5. In vivo studies in BALB/c mice included pharmacokinetic studies to inform an appropriate dosing regimen. Finafloxacin efficacy was evaluated in an inhalational murine model of melioidosis where antibiotic treatment was initiated at 6 or 24 h postchallenge and continued for 14 days, and mice were observed for 63 days. The survival of infected mice following 14 days of treatment was 80%, 60% or 0% for treatments initiated at 6 h and 60%, 30% or 0% for treatments initiated at 24 h for finafloxacin, co-trimoxazole, or ciprofloxacin, respectively. In summary, finafloxacin has increased bactericidal activity for B. pseudomallei under acidic conditions in vitro and improves survival in a murine model of melioidosis compared with those for ciprofloxacin. Furthermore, finafloxacin improves bacteriological clearance compared with that of co-trimoxazole, suggesting it may offer an effective postexposure prophylaxis against B. pseudomallei.